2015
DOI: 10.1007/s12570-015-0317-z
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a properly positioned tantalum rod for treatment of early femoral head necrosis and conversion to total hip arthroplasty

Abstract: Background Conventional core decompression (CD) is a well-known procedure for treatment of avascular necrosis of the femoral head. Weight bearing is usually restricted in the early postoperative weeks to avoid the risk of fracture. Theoretically, a properly positioned implantation of the new tantalum rod after reaming of the necrotic area has the advantages of decompression, supports the remaining bone to avoid collapse, lowers the risk of subtrochanteric fracture, and allows for early weight bearing. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…More importantly, the gradually changed pore size can contain the optimal size and porosity for bone ingrowth. For some early implantation failure in dental and orthopaedic applications, the implants with poor stability and lack of complete bone ingrowth are high-risk factors [7], [8]. The space in the scaffolds has a momentous role in osteogenesis and vascularisation, which can lead to biological fixation at an early stage of bone healing [43].
Figure 9The internal stress transmission of (A) D1, (B) D2, (C) D3 and (D) a homogeneous porous scaffold.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the gradually changed pore size can contain the optimal size and porosity for bone ingrowth. For some early implantation failure in dental and orthopaedic applications, the implants with poor stability and lack of complete bone ingrowth are high-risk factors [7], [8]. The space in the scaffolds has a momentous role in osteogenesis and vascularisation, which can lead to biological fixation at an early stage of bone healing [43].
Figure 9The internal stress transmission of (A) D1, (B) D2, (C) D3 and (D) a homogeneous porous scaffold.
…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the bone tissues can become atrophic and gradually lose the load-bearing capability, which may cause osteoporosis and fracture around the implants [6]. In addition, the bone resorption around the implants can lead to an unstable interface between bone and implants, which can be regarded as the high risk for early implantation failure [7], [8]. To address these issues and to construct a long-lasting implant, the porous design is introduced to mimic the elasticity modulus and yield the strength of the nature bone [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the in vivo study have confirmed this point of view. For some early implantation failure in dental and orthopedics, the implants with poor stability and lack of complete bone ingrowth are high risk factors (58,59). The histological evaluations demonstrated that new bone tissues were evenly distributed inside and around the scaffolds, and the PDA coating titanium scaffolds can acquire superior bone ingrowth in a short time-period.…”
Section: Discussionmentioning
confidence: 99%
“…Во избежание резорбции окружающей костной ткани имплантат должен иметь пористую структуру [5,6], способствующую миграции и пролиферации остеобластов и мезенхимальных стволовых клеток, транспортировке питательных веществ и кислорода, необходимых для васкуляризации во время роста костной ткани [7,8]. По данным литературы, размер пор и структура также влияют и на остеокондукцию [9,10].…”
Section: Introductionunclassified